Regional Spillover Effects of Mataram City Growth on Economic Development in Lombok Barat Regency, Indonesia - Rizkia Rahmawati Putri; Sahri , Sahri; Masrun, Masrun; Yu Kong; Shichang Shen; Pablo Mendieta Ossio (Tinta Emas Publisher, 2024)
This research aims to analyze the spillover effect of Mataram City's growth center on the economic growth rate of the hinterland region, specifically Lombok Barat Regency. The independent variables include domestic investment in Mataram City (X1) and Mataram City's economic growth rate (X2), while the dependent variable is the economic growth rate of Lombok Barat Regency (Y). The study utilizes time-series secondary data from publications by the Central Statistics Agency (BPS) and other relevant agencies in Nusa Tenggara Barat, covering the period from 2010 to 2022. The Ordinary Least Squares (OLS) method is employed for analysis. The findings reveal that the independent variables in this study account for 98.50 percent of the variance in the dependent variable, while the remaining 1.50 percent is influenced by factors outside the estimation model. On a partial basis, domestic investment in Mataram City does not have a significant effect on the economic growth rate of Lombok Barat Regency, indicating that this variable does not contribute to a positive economic spillover effect. However, the economic growth rate of Mataram City has a positive and significant impact on the economic growth of Lombok Barat Regency, suggesting that it contributes a positive spillover effect. Simultaneously, the combined influence of domestic investment and Mataram City's economic growth rate has a positive spillover effect on Lombok Barat Regency’s economy.